Pathogenic variants in SMARCA5, a chromatin remodeler, cause a range of syndromic neurodevelopmental features - Li, Dong; Wang, Qin; Gong, Naihua N.; Kurolap, Alina; Feldman, Hagit Baris; Boy, Nikolas; Brugger, Melanie; Grand, Katheryn; McWalter, Kirsty; Sacoto, Maria J. Guillen; Wakeling, Emma; Hurst, Jane; et al. (Science advances, 2021)
Intellectual disability encompasses a wide spectrum of neurodevelopmental disorders, with many linked genetic loci. However, the underlying molecular mechanism for more than 50% of the patients remains elusive. We describe pathogenic variants in SMARCA5, encoding the ATPase motor of the ISWI chromatin remodeler, as a cause of a previously unidentified neurodevelopmental disorder, identifying 12 individuals with de novo or dominantly segregating rare heterozygous variants. Accompanying phenotypes include mild developmental delay, frequent postnatal short stature and microcephaly, and recurrent dysmorphic features. Loss of function of the SMARCA5 Drosophila ortholog Iswi led to smaller body size, reduced sensory dendrite complexity, and tiling defects in larvae. In adult flies, Iswi neural knockdown caused decreased brain size, aberrant mushroom body morphology, and abnormal locomotor function. Iswi loss of function was rescued by wild-type but not mutant SMARCA5. Our results demonstrate that SMARCA5 pathogenic variants cause a neurodevelopmental syndrome with mild facial dysmorphia. - Exome sequencing and Drosophila modeling revealed variants in SMARCA5 as a novel cause of a neurodevelopmental disorder. - Exome sequencing and Drosophila modeling revealed variants in SMARCA5 as a novel cause of a neurodevelopmental disorder.
Gesehen am 15.07.2021